FACTORS INFLUENCING TEENAGE PREGANANCY AMONG GIRLS AGED 13-19 YEARS ATTENDING ANTENENTAL CARE AT NKONI HEALTH CENTRE III LWENGO DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Namiiro , Gorreth (Student’s Journal of Health Research Africa, 2024)
Introduction. Adolescent pregnancy is defined as a pregnancy in girls, 10–19 years of age. An estimation of 16 million girls aged 15–19 years old give birth each year, contributing to nearly 11% of all births worldwide. Globally, approximately 18 million girls under 20 years give birth each year. In Lwengo was reported to be 4.7% births per woman in 2022, higher than Uganda‘s estimated of 25%. Purpose of the study. To increase knowledge and create awareness about teenage pregnancy and its related consequences. Objectives. The general objective of the study was to determine factors influencing teenage pregnancy among girls aged 13 -19 years attending antenatal care at Nkoni health center III which encompassed knowl- edge, cultural practices, and social-economic factors. Methodology. This descriptive cross-sectional study was conducted from 5th - 27th January 2023 where 153 par- ticipants were selected at convenience, and issued questionnaires to ensure data collection which was presented in the form of tables, pie charts, charts, and figures. Results. The study showed that majority, 80(52.3%) of the respondents were aged 17-19 years, 110(71.8%) had knowledge about SRH which they acquired from Relatives, and the age of conception was above 14 years, however, they did not know the fertile period, 82(53%) did not use contraceptives, alcohol use (17%), watching pornography 40(67%), 35(58%) transactional sex and most parents were peasants. Conclusion Most female adolescents had good knowledge about SRH; Poverty increased the risk of teenage pregnancy. Recommendations. The local government should work collaboratively with citizens to eradicate poverty through sensi- tization and motivation, as well as setting up projects to advance peasant farmers. Also, involve the religious leaders to counsel parents about the upbringing of children, and setting up tough laws on convicts. Parents should motivate teenagers to stay in school to prevent teenage pregnancy.